Knowledge, perception, and public attitude on biotech crops in Indonesia - Dahri Tanjung; Yeti Lis Purnamadewi; Bambang Purwantara; Dewi Suryani (Agriekonomika, 2025)
Until now, many genetically engineered products have met our basic needs and provided various benefits. However, there are still many who doubt or even reject them. This raises the question of how the public's knowledge and understanding of these biotechnological plants stand. This research aims to analyze whether public actions in adopting biotechnology are influenced by their knowledge and perceptions. This survey used a questionnaire with 535 respondents. The results show that about 70% of respondents have limited knowledge about biotechnology, with information channels including print media, social media, and interpersonal communication. About 75% of respondents agree that biotechnology can enhance agricultural productivity, the economy, and farmers' welfare, as well as contribute to food security. Furthermore, 76% of respondents agree to purchase these products. PLS-SEM analysis reveals a strong positive relationship between knowledge, perceptions, and positive attitudes toward biotechnology products. Therefore, enhancing information dissemination through various alternative media and involving stakeholders need to be strengthened in the future.